Refeeding Syndrome and Its Related Factors in Critically Ill Coronavirus Disease 2019 Patients: A Prospective Cohort Study - Vahdat Shariatpanahi, Zahra; Vahdat Shariatpanahi, Maryam; Shahbazi, Erfan; Shahbazi, Shaahin (Frontiers in Nutrition, 2022)
Background and Aim Malnutrition and its complications is usually neglected in critically ill COVID-19 patients. We conducted the present study to investigate the prevalence of refeeding syndrome and its related factors in this group of patients. Methods In this prospective cohort study, 327 patients were assessed for being at risk and developing refeeding syndrome. The criteria was ASPEN consensus recommendations for refeeding syndrome released in 2020. Malnutrition was assessed based on global leadership initiative on malnutrition (GLIM) criteria. The relation between actual protein, calorie intake, and refeeding syndrome was also evaluated via cox regression model. The data concerning calorie and protein intake were gathered for 5 days after initiating feeding. The daily protein and calorie intake were divided by kilogram body weight in order to calculate the actual protein (g/kg/day) and energy (kcal/kg/day) intake. Results Among the subjects, 268 (82%) were at risk of refeeding syndrome and 116 (36%) got involved in this syndrome. Malnutrition, according to the GLIM criteria, was found in 193 (59%) of the subjects. In the at-risk population, the risk of refeeding syndrome was reduced by 90% with the rise in protein intake (CI; 0.021–0.436, P = 0.002), increased by 1.04 times with the increase in age (CI; 1.032–1.067, P < 0.001), and by 1.19 times with the rise in the days from illness onset to admission (CI; 1.081–1.312, P < 0.001) in adjusted cox model analysis. Conclusion The incidence of refeeding syndrome is relatively high, which threatens the majority of critically ill COVID-19 patients. Increased protein intake was found to reduce the occurrence of refeeding syndrome.